FACTORS OF NON-PERFORMING LOANS ON PARTNERSHIP PROGRAM OF COMMUNITY DEVELOPMENT CENTER (Case Study on PT TELKOM Tbk Kandatel Malang) - Yusuf, Heidy Atho’illah (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to finding the factors that cause non-performing loans in partnership program of CDC PT Telkom Kandatel Malang. The data from CDC PT Telkom Kandatel Malang shows that there are decreasing percentage level of loan repayment. This study classified as qualitative descriptive study. Case study is employed as the research method to answer the research questions. Furthermore, the data collection methods used in this study are interview, documentation and observation. The result in this study reveals the factors that cause non-performing loans in partnership program of CDC PT Telkom Kandatel Malang are internal factors and external factors. The internal factors of non-performing loans in partnership program of CDC are difficulty in predict the ‘character’ of candidate partners, lack of human resources in CDC team to survey candidate partners and lack of monitoring the partners. The external factors of non-performing loans in partnership program of CDC are partners cannot compete with the market, the condition of Indonesia economy or changes in government policy and regulations that affect the business, partners did not make notes to record amount of money to pay the loan, partners did not submit business progress report for every 3 months to CDC, misappropriation committed by partners in utilizing loan, dishonesty of partners, partners do not have good intentions to pay the loan and the illness or health condition of partners.Key words: Non-performing loans, Partnership Program, Community Development Center, Corporate Social Responsibility, PT Telekomunikasi Indonesia Tbk.